RANCANG BANGUN APLIKASI SELULER PENYEDIA JASA PERAWATAN DAN KECANTIKAN MENGGUNAKAN FRAMEWORK FLUTTER - Jauzaa Maylia Suhendro; Made Sudarma; Duman Care Khrisne (Program Studi Teknik Elektro UNUD, 2021)
The development of technology in this era of globalization has provided many benefitsin human life, one of which is smartphones. In this modern era, looking neat and attractive is adaily necessity for people, especially women. To get beauty care services, people usually haveto look salons and wait their turn. This takes a long time for beauty care service enthusiasts.Based on the existing background, a beauty care service provider application design was builtusing the flutter framework and android operating system with the aim of making it easier forusers to find care and beauty services. In this application there are 3 users, namelyAdministrators who are in charge of controlling Customer and Partner data, Customers as userswho are looking for care and beauty services, and Partners as people who offer care andbeauty services. Based on tests carried out using the Black Box method, the overallfunctionality of the application has been declared successful in accordance with its respectivefunctions and objectives. While the test results using the System Usability Scale (SUS) methodin the application, respondents gave a score with an average value of 73.75 which means thatthe test results have a value above average. It can be concluded that the application can runwell and can be Accepted (Acceptable).